Cover Feature: Unravelling Structural Mysteries of Simple Organozinc Alkoxides (Chem. Eur. J. 18/2021). Issue 18 (28th January 2021) - Mąkolski, Łukasz; Szejko, Vadim; Zelga, Karolina; Tulewicz, Adam; Bernatowicz, Piotr; Justyniak, Iwona; Lewiński, Janusz
Abstract : Ladies and gentlemen ! Unique structural motifs of simple RZnOR' alkoxides, a roof‐like trimer and a ladder‐type tetramer, are presented to the broad audience of chemists. Moreover, we show that when our ′chemical performance′ is undertaken in solution, organozinc alkoxides undergo Schlenk‐type ligand redistribution processes, providing the trinuclear spiro‐type compounds. The announced results thus make sure that this long‐standing organometallic show is continuously going on. More information can be found in the Full Paper by J. Lewiński et al. on page 5666 .